2021
DOI: 10.2217/bmm-2020-0776
|View full text |Cite
|
Sign up to set email alerts
|

Sialic Acid As A Potential Biomarker for Cardiovascular Disease, Diabetes and Cancer

Abstract: Cardiovascular disease (CVD), diabetes and cancer pose increasing global healthcare burdens. New biomarkers could enable earlier diagnosis of these diseases, leading to more effective treatment and lower associated healthcare burden. Elevated sialic acid concentration in plasma and serum has been positively correlated with the presence of CVDs, diabetes and the development of malignant tumors. This article reviews the use of total sialic acid (TSA), bound sialic acid (BSA) and free sialic acid (FSA) as potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 74 publications
1
15
0
Order By: Relevance
“…354 A study by Cheeseman et al revealed that elevated concentrations of sialic acids in plasma and serum correlated positively with the presence of CVD, diabetes, and the development of malignant tumors. 344 Another study by Laider et al found a significant correlation between increased α2,6sialylation and adhesion abilities of metastatic melanoma cells. 355 In line with these observations, Kremser et al, identified an altered N-glycome by MALDI-MS on integrins α3β1 and α5β3 and revealed that glycan modifications have been related with increased melanoma cell motility, impacting cell−ECM interactions.…”
Section: Ht-glycomics In Clinical Studiesmentioning
confidence: 96%
See 1 more Smart Citation
“…354 A study by Cheeseman et al revealed that elevated concentrations of sialic acids in plasma and serum correlated positively with the presence of CVD, diabetes, and the development of malignant tumors. 344 Another study by Laider et al found a significant correlation between increased α2,6sialylation and adhesion abilities of metastatic melanoma cells. 355 In line with these observations, Kremser et al, identified an altered N-glycome by MALDI-MS on integrins α3β1 and α5β3 and revealed that glycan modifications have been related with increased melanoma cell motility, impacting cell−ECM interactions.…”
Section: Ht-glycomics In Clinical Studiesmentioning
confidence: 96%
“…Recently, glycobiology has gained importance in cancer research given its role in understanding various cancer mechanisms and for diagnostic application. Also, advances in the field of proteomics and glycomics have helped glycobiologists decipher the link between glycan structures and disease progression . Glycosylation acts as a key regulatory mechanism, controlling several physiopathological processes and defects in glycosylation are associated with various diseases, including cancers. , While glycoproteins are some of the most common clinically used biomarkers for diagnosis and monitoring of malignant progression, their glycosylation has not, yet, been taken into account. , However, it has been widely shown that glycosylation changes can be associated with cancer, of which most are related to sialylation, fucosylation, mucin-type O -glycans, as well as N - and O -linked glycan branching. ,, …”
Section: Applicationsmentioning
confidence: 99%
“…Both mutations have been shown to increase sialyltransferase activity in vitro, possibly in vivo. Increased sialyltransferase activity in blood cells and serum sialic acid levels are associated with atherosclerosis and CAD [ 64 ]. Some studies in the United States have provided statistically significant additional evidence for the potential contribution of ST6GALNAC5 gene mutations to the occurrence of CAD [ 63 ].…”
Section: Monogenic Etiology Of Cad/mimentioning
confidence: 99%
“…[14,16] Neu5Ac has previously been identified as a biomarker for cancer, diabetes and cardiovascular diseases. [17] Overexpression of sialic acid has been detected on the endothelium when cardiovascular disease (CVD) and therefore inflammation is present. There is a significant elevation in sialic acid in plasma and serum samples between healthy controls and disease patients.…”
Section: Introductionmentioning
confidence: 99%
“…Neu5Ac has previously been identified as a biomarker for cancer, diabetes and cardiovascular diseases [17] . Overexpression of sialic acid has been detected on the endothelium when cardiovascular disease (CVD) and therefore inflammation is present.…”
Section: Introductionmentioning
confidence: 99%